IMPLEMENTASI BUDIDAYA MAGOT SEBAGAI UPAYA PENGELOLAAN SAMPAH ORGANIK PADA PROGRAM KKN UNIVERSITAS PGRI MAHADEWA INDONESIA DI DESA SINGAPADU BANJAR BUNGSU - ina nambo; Magdalena Ina; Stepanus Jamanunna; Suryadi Umbu Gaga; Gede Sidi Artajaya; Gusti Ngurah Agung Cahya Prananta; Ni Kadek Dwi Lestari (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2026)
The problem of organic waste is becoming an increasingly complex environmental issue, especially in rural areas that still use conventional management methods. This study aims to analyze the implementation of maggot cultivation as an organic waste management effort in the Real Work Lecture (KKN) program of the University of PGRI Mahadewa Indonesia in Singapadu Village, Banjar Bungsu. The method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that maggot cultivation (Black Soldier Fly/BSF larvae) can significantly reduce the volume of organic waste by utilizing household waste as the main feed. In addition, this program also increases public awareness of the importance of sorting-based waste management and encourages active community participation in protecting the environment. Another impact generated is the economic potential through the use of maggots as animal feed and a commodity with a market value.